IDENTIFYING A REPRESENTATIVE SOUVENIR FOR A ROMANIAN TOURIST DESTINATION. THE CASE OF RUPEA - ISPAS, Ana; UNTARU, Elena Nicoleta; IEȘANU, Stela (Annales Universitatis Apulensis Series Oeconomica, 2014)
Creating a souvenir is a large and complex process that relies on the identification of a representative, unique and authentic element for the promoted tourist destination. A souvenir is a tangible product - a symbol of the visited area, the experience at the destination and the memory kept on returning from holiday. This paper aims to investigate the views of representatives of the City Hall of Rupea and of the Association for the Promotion and Development of Tourism in Brașov (APDT) on the opportunity of conceiving of a representative souvenir for the tourist destination of Rupea, using the focus group as a qualitative research. The research results showed that the souvenir that would best represent the tourist destination Rupea is Rupea Fortress, this being the most important monument in the city.